Pomoże ktoś szybkooo ​

Pomoże Ktoś Szybkooo class=

Odpowiedź :

(3-2x)-(x+3)=(x-5)-(-3-x)

3-2x-x-3=x-5+3+x

-3x-3=2x-5

-3x-2x=-5+3

-5x=-2 |:(-5)

x=2/5

===========================

(3-2x)-(x+4)-(2x+5)=(3x-4)-(5x+7)

3-2x-x-4-2x-5=3x-4-5x-7

3-2x-x-2x-5=3x-5x-7

-2-5x=-2x-7

-5x+2x=-7+2

-3x=-5 |:(-3)

x=5/3

x=1 2/3

===========================

3(x-4)-4(2x-7)=2(x+5)

3x-12-8x+28=2x+10

3x-8x-12+28=2x+10

-5x+16=2x+10

-5x-2x=10-16

-7x=-6 |:(-7)

x=6/7

===========================

3(3-x)+2x=8-2(x-1)

9-3x+2x=8-2x+2

9-x=8+2-2x

9-x=10-2x

-x+2x=10-9

x=1